ISMAIL, Rahil, SHAW, Brian and OOI, Giok Ling. Eds. 2009. Southeast Asian Culture and Heritage in a Globalising World. Surrey, UK: Ashgate, pp. 1–173. ISBN: 978-0-7546-7261-6. (KEMANUSIAAN The Asian Journal of Humanities, 2010)
This collection of nine conference papers deals with the problems of the "pluralistic nation-state" in Southeast Asia, its cities, environmental crises, human rights issues and problems relating to cultural heritage and identity in the face of globalisation. The societies under study—Malaysia, Singapore, Indonesia, Laos and Burma—all have a diverse mix of ethnic peoples and hybrid cultures, in which the cultures of minority groups are confronted by accelerating social change and experience institutionalised oppression, fragmentation and political threats from the dominant ethnic groups. Interdisciplinary in their approach, and falling well into the field of multi-cultural studies, the paper writers represent a range of disciplines, from geography, sociology, history to cultural studies. The geographers who are in the majority, attempt to deal with the issues of community, environment, tourism, conservation and urban-rural development, while the social scientists focus on education, the economy, health and public housing.